Undergraduate Students’ Perception of the Use of WhatsApp-Based Speaking Instructional Materials - Maulina Maulina; Hastianah Hastianah; Herianah Herianah (Indonesian TESOL Journal, 2023)
WhatsApp-based speaking instructional material (WABSIM), a social media-integrated teaching and learning form, is a much-needed and highly demanded speaking resource for students to access and learn English in flexible ways. This study was conceived to figure out students’ responses to the use of WABSIM for learning basic speaking. Twenty eight English Education Department students filled out a Google Forms questionnaire assessing the indicators of experience, motivation, and attitude. This current study reveals the perception of use of WABSIM; in terms of experience, 64.3% of students agree that it has helped enrich their insight, and 53.6% of students agree that it promotes an enjoyable learning situation. In the motivation aspect, 57.1% of students agree that they feel motivated in studying speaking skills using the WABSIM, 53.5% of students enjoy the WhatsApp-based communication tasks, 67.9% are willing to study speaking using WABSIM, and 50% agree that speaking lessons during the semester were fun. In terms of attitude indicators, half of the students agree that the WABSIM could increase their self-confidence in speaking English about daily topics, and that they became more active in learning – it helped them to learn the course independently and collaboratively. Therefore, the research indicates that students favourably perceive the use of WABSIM for learning in flexible ways inside and beyond the classroom, and that the learning through the WhatsApp instructions, such as recording audio and video material, as well as making audio and video calls, encourages students to be collaborative and even more independent.Keywords: WhatsApp, social media, speaking skill, mobile learning, motivation, students’ perceptions